Study on adolescent gynaecological problems - Bhakti V Kalyankar; Vijay Y Kalyankar; Shrinivas Gadappa; Megha Chauhan (Barpeta Obstetrics and Gynaecological Society, 2023)
Background: Adolescent is age between 11-19 years, where there are enormous physical, psychological, sexual, emotional and behavioural changes. They constitute 22 % of population in India. Hence, their unique problems need to be addressed. Objectives: 1) To study gynaecological problems and their clinical profile in adolescent girls. 2) To evaluate treatment modalities of gynaecological problems in adolescent girls. 3) To evaluate reproductive health awareness among adolescent girls. Methods: Girls in the age group of 11 to 19 years attending gynaecology OPD or emergency were included in the study. First, the girl was interviewed keeping her privacy and dignity. A detailed history and examination were done emphasizing on pubertal events such as thelarche, pubarche, pregnancy and menarche. Investigations like hemogram, coagulograms, hormonal assays, and sonography were done wherever applicable. Results: 71.67% achieved menarche at 14-16 years of age. Most common gynaecological problems among the adolescent girls were menstrual disorders 156 (52%), followed by vaginal discharge i.e. 35(11.6%), 24(8.0%) gave history of sexual assault, 24 (8%) had excessive weight gain and 20(6.6%) reported urinary tract infection. The most common type of menstrual disorder was that of oligomenorrhea 86 (55.2%). Out of 38 PCOS cases, 31(81.6%) cases presented with oligomenorrhea. Out of 300 cases, 200(66.7%) cases were aware of physical signs of puberty, 245(81.7%) cases were aware of STD, HIV and its mode of transmission, 200(66.7%) cases were aware about contraceptive methods, 150(50.0%) cases were aware about physiology of menstruation and 198(66.0%) cases were aware of menstrual hygiene. Out of 19 teenage pregnancies, in 8(42.1%) cases LSCS was done, 4(21.3%) cases had vaginal delivery and 4(21.0%) cases had MTP. Conclusions: Menstrual abnormalities are the most common gynaecological problems of adolescents. Adolescents should be addressed with dignity. It is need of the time to set up specialized adolescent gynaecological clinics.